Unique Mutation in SP110 Resulting in Hepatic Veno-Occlusive Disease with Immunodeficiency - Osama Hamdoun; Asia Al Mulla; Shamma Al Zaabi; Hiba Shendi; Sharifa Al Ghamdi; Jozef Hertecant; Amar Al-Shibli (Hindawi Limited, 2020)
Familial hepatic veno-occlusive disease with immunodeficiency (VODI, OMIM: 235550) is a rare form of combined immune deficiency (CID) that presents in the first few months of life with failure to thrive, recurrent infections, opportunistic infections along with liver impairment. Herein, we are describing a Pakistani patient with a homozygous novel variant in the SP110 gene, presenting with classical phenotypic manifestations of VODI. He presented at the age of 3 months with opportunistic infections and later developed liver failure. Conclusion. Hepatic veno-occlusive disease with immunodeficiency is a rare cause of immunodeficiency, and this is the first case report from the Middle East in a patient of Pakistani origin. It is important to have a high suspicion for this disease, in patients presenting early life with a picture of CID and deranged liver function, as the earlier the diagnosis and treatment, the better the prognosis.